Physical Violence and Associated Factors among Housemaids Living in Debre-Tabor Town, Northwest Ethiopia: Does Employer Alcohol Intake Increase Housemaid Violence? - Azanaw, Kefyalew Amogne; Gelagay, Abebaw Addis; Lakew, Ayenew Molla; Teshome, Destaw Fetene (International Journal of Reproductive Medicine, 2019)
Background. Violence against women and girls continues to be a global epidemic, including Ethiopia. Housemaids are a neglected segment of the population, and there are no sufficient findings in our country. This study aimed to assess the magnitude of physical violence and associated factors among housemaids aged 15 years and above living in Debre Tabor town, northwest Ethiopia. Methods. A community-based cross-sectional study was conducted in Debre Tabor town, northwest Ethiopia from April 1 to 30, 2018. A total of 634 housemaids were selected using cluster sampling method. Data were entered into Epi info version 7.2.2.6 and analyzed with SPSS version 20 using descriptive and analytic statistics. Binary logistic regression analysis was carried out to identify independent significant factors. Adjusted odds ratio (AOR) with 95% confidence interval (CI) was used to report the strength of associations. Results. From 634 housemaids that participated in the study, 235 (37.1%, 95% CI: 33.1−41.0) of them experienced at least one type of physical violence in their lifetime. Housemaids who previously lived in rural areas (AOR=2.82, 95% CI: 1.61, 4.94), had high working experience (AOR=2.17, 95% CI: 1.27, 3.71), not having parents (AOR=2.02, 95% CI: 1.18, 3.46), being divorced (AOR=2.23, 95% CI: 1.31, 4.20), employer alcohol consumption (AOR=4.97, 95% CI: 2.81, 8.79), and presence of extended family with employers (AOR=2.26, 95% CI: 1.42, 3.59) were independently associated with the probability of housemaid physical violence. Conclusion. High prevalence of housemaid physical violence has been reported. Socio-demographic characteristics of both employers and employees and the behavioral characteristics of employers contributed to physical violence. It is important to give special attention to housemaids who came from rural areas and do not have parents. It is also important to make work experience of housemaids as short as possible.